Islamic Financial Literacy In Digital Age: The Role Of Social Capital And Digital Literacy - Herawati, Mesi; Mukhsin, Muhamad (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study investigates the influence of digital literacy and social capital on Islamic financial literacy among millennials in Indonesia, focusing on their ability to utilize digital platforms and social networks for financial education and decision-making in accordance with Islamic principles.Design/methodology: Using a quantitative approach, primary data was collected from 270 respondents fitting the criteria of Indonesian students who use Islamic financial services. Data analysis employed the multiple linear regression method using SmartPLS 4.0. Reliability and validity tests, along with hypothesis testing, were conducted to assess the relationship between digital literacy, social capital, and Islamic financial literacy.Findings: The findings reveal that both digital literacy and social capital positively and significantly influence Islamic financial literacy. Digital literacy enhances individuals' access to Islamic financial information through digital platforms, while social capital facilitates knowledge-sharing and trust within communities, further reinforcing financial literacy levels.Practical implications: The study emphasizes the need to leverage digital technologies and strengthen community-based approaches to improve Islamic financial literacy. Stakeholders, including educational institutions and financial service providers, should integrate digital literacy education and promote community engagement to foster Islamic financial literacy.Originality/Value: This research contributes to the limited body of knowledge on the interplay between digital literacy, social capital, and Islamic financial literacy, particularly in a digital era context. It offers strategic insights for enhancing financial literacy within Islamic frameworks through technological and social interventions.